Metode Baru untuk Menghubungkan Peserta Didik dengan Iman Kristen - Lie, Romi (Jurnal Kala Nea, 2022)
Innovation in Christian Religious Education can create a more effective and engaging learning process for students, develop relevant skills and competencies, and increase students' interest and participation in Christian Religious Education. The main purpose of innovation in Christian Religious Education in the digital era is to create or discover methods/approaches that are more relevant and engaging for students in learning about Christianity. The method used in this research is literature review. This research method is used to find new methods to connect students with their faith through innovation in Christian Religious Education in the digital era. The benefits of innovation in Christian Religious Education in the digital era are to increase the effectiveness of learning Christian Religious Education, develop relevant skills and competencies, and increase students' interest and participation in Christian Religious Education. With innovation in Christian Religious Education in the digital era, students can connect with their faith and beliefs more effectively and authentically.